Disfunção endotelial precoce em pacientes com lipodistrofia generalizada congênita (síndrome de berardinelli-seip) avaliada por dilatação fluxo-mediada da artéria braquial e tonomeria arterial periférica - Fernandes, Virginia Oliveira (2015)
Congenital generalized lipodystrophy (CGL) is a rare, autosomal recessive disease, characterized by total or almost total absence of adipose tissue since birth. Mutations in the BSCL1/AGPAT2 and BSCL2/Seipin genes account for 95% of cases. CGL courses with severe insulin resistance (IR), diabetes mellitus (DM) and dyslipidemia, which may culminate in atherosclerosis and premature cardiovascular mortality. However, there is a lack of studies evaluating early vascular damage in this condition. This study aimed to determine the prevalence of endothelial dysfunction (ED), through assessment of flow-mediated dilation (FMD) of the brachial artery and peripheral arterial tonometry (PAT), and its association with genotypic and phenotypic characteristics in population with CGL. We evaluated 11 patients with CGL, 11 with metabolic syndrome (MS) and 22 healthy controls, matched for sex and age. We performed clinical and laboratory evaluation, abdominal ultrasonography, echocardiography, molecular study of AGPAT2 and BSCL2 genes and evaluation of endothelial function by FMD (by the % of the brachial artery dilation -%FMD) and PAT (by reactive hyperemia index - RHI). In the CGL, MS and control groups, age (years) was, respectively, 10 (5-30), 13 (11-19) and 12 (10-19) and were female, 63.5%, 68.2% and 54.1%. There was a higher prevalence of hypertriglyceridemia, hypercholesterolemia, DM, BP above the 95 percentile (p<0.001) and low HDL-c (p=0.013). The MS group differed from the CGL group by the absence of DM and higher BMI (p=0.001). Among the CGL, 45.5% were BSCL2 mutants and 18.2% AGPAT2 (36.3% without genetic study). Of these, all had hypoleptinemia (1.1ng/ml, 0.8-1.7), hypertriglyceridemia and low HDL-c; 63.6% had DM, 54.5% hypercholesterolemia, 45.5% hepatic steatosis, 45.5% nephropathy and 36.4% hypertrophy of the left ventricle. In the CGL group, 81.9% had FMD<10% and 63.6% RHI<1.67, featuring ED. The % FMD in this group was lower compared with the MS, 8.0% (2.9-10.3) vs. 13.0% (6.9-28.1; p=0.003) and controls, 16.0% (10.0-30.0, p=<0.001). The basal brachial artery diameter (BBD) was higher in the CGL group compared to the MS (p=0.041) and control (p=0.015) (suggesting more severe ED). The %FMD was also lower among individuals with CGL and DM (7.1%; 8.9% vs. 2.9-10.3; 5.2-10.3) and BSCL2 mutants vs. AGPAT2 (5.3%; 2.9-10.3 vs. 7.9%; 7.1-8.7). CGL and control groups assessed PAT. The CGL group showed less reactive hyperemia index (RHI), 1.7 (0.8-2.3) vs. control group, 2.1 (1.7-3.0; p <0.001) and greater PAT- AIx than the control (p=0.023) (suggesting increased arterial stiffness). The ED was more prevalent among BSCL2 mutants and those with DM. There was a negative correlation between %FMD and BBD; %FMD and triglycerides; RHI and triglycerides and positive between %FMD and RHI with HDL-c. The concordance of the results of FMD and PAT was 63.6%. In conclusion, ED, evaluated by both FMD, and PAT was condition of very high prevalence in the CGL, observed in most subjects from this significant Brazilian series. In this condition, ED is presented earlier and with more severe characteristics,. The hyperglycemia, dyslipidemia (low HDL-c and hypertriglyceridemia) were strongly associated with ED. These factors, as well as severe IR and hipoleptinemia, quite prevalent in this syndrome and that typically affect early on individuals with CGL, could justify the greater impairment of endothelial function in this disease. It is noteworthy that ED was more prevalent in patients BSCL2 mutants, which typically have more severe forms of the disease. The agreement between diagnosis in ED by FMD and PAT suggests that both methods are valid in the investigation of endothelial dysfunction, but possibly complementary.